Estrategias pedagógicas alternativas para el desarrollo de habilidades comunicativas en los niños de 4 a 5 años. - Basantes Moreano, Verónica Maricela (2022)
Research on alternative pedagogical strategies facilitated reaching significant experiences in the child's development, mainly in their communication skills that involve their socialization and integration in the different contexts in which they develop, according to their level and with the research objective set: Apply the guide of alternative pedagogical strategies for the strengthening of oral communication in children from 4 to 5 years old. To comply with it, field research is carried out, such as the survey of parents, teachers and direct observation of twenty-five children in the educational center. It was used for theoretical support, bibliographical and field research, together with the qualitative-quantitative methodology that allowed scientifically documenting the variables that were the subject of the investigation. As for the direct beneficiaries, they were the children and parents of the Educational Institution. In relation to the results, it was evidenced that the application of the proposal with workshops from phonological, semantic, pragmatic and syntactic awareness combined the processes of oral communicative development in children through songs, games, videos that allowed the child to express themselves and communicate. with the world with a series of signs and organized symbol systems, through which they were able to express what they live, think, desire and feel, since it was shown that orality begins in the family through the contacts, gestures and words of all , between parents and their children and therefore manifest in the educational community.